The Vice Chancellor in Australian Universities: Understanding Leadership Beyond 'Bad Apples' and 'Unicorns' - Jamie Quinton; Tara Brabazon (Ali Khorsandi Taskoh, 2022)
Leadership in Australian higher education has confronted crises, threats, restructures, and embarrassment. From sexual harassment claims to nepotism, regulatory authorities have investigated individual Vice Chancellors and their behaviour. Such crises reveal the consequences of decision making and appointment processes. While COVID-19 demonstrated the institutional reliance on international students to ensure financial security, these weaknesses existed long before the pandemic. Through this troubled time, are there patterns or priorities that 'create' a Vice Chancellorship? How do researchers understand leadership in our universities, beyond 'a few bad apples' - to describe the excesses and improprieties - or the 'unicorns' that have trotted the golden path to success? This article arches beyond the individual cases that become tabloidized headlines. Instead, we probe if there are shared characteristics among Vice Chancellors, evaluating how career progression emerges in the higher education sector. This article also assesses the consequences of this leadership pathway on universities, particularly for building a post-pandemic future.